The most common European HINT1 neuropathy variant phenotype and its case studies - Rozevska, Marija; Rots, Dmitrijs; Gailite, Linda; Linde, Ronalds; Mironovs, Stanislavs; Timcenko, Maksims; Linovs, Viktors; Locmele, Dzintra; Micule, Ieva; Lace, Baiba; Kenina, Viktorija (Frontiers in Neurology, 2023)
HINT1 is a ubiquitous homodimeric purine phosphoramidase belonging to the histidine-triad superfamily. In neurons, HINT1 stabilizes the interaction of different receptors and regulates the effects of their signaling disturbances in axonal signaling. Disease associated changes in HINT1 gene are associated with autosomal recessive axonal neuropathy with neuromyotonia. Aim of the study was detailed description of patients’ phenotype with HINT1 homozygous NM_005340.7: c.110G>C (p.Arg37Pro) variant. Seven homozygous and three compound heterozygous patients were recruited and evaluated using standardized tests for CMT patients, in four patients’ nerve ultrasonography was performed. The median age at symptom onset was 10 years (range 1-20), with initial complaints being distal lower limb weakness with gait impairment, combined with muscle stiffness, more pronounced in the hands than in the legs and worsened by cold. Arm muscles became involved later, presenting with distal weakness and hypotrophy. Neuromyotonia was present in all reported patients and is thus a diagnostic hallmark. Electrophysiological studies demonstrated axonal polyneuropathy. Impaired mental performance was observed in six out of ten cases. In all patients with HINT1 neuropathy, ultrasound examination showed significantly reduced muscle volume as well as spontaneous fasciculations and fibrillations. The nerve cross-sectional areas of the median and ulnar nerves were closer to the lower limits of the normal values. None of the investigated nerves had structural changes.